Calcitriol levels and the stage of chronic kidney disease in children - Diska Yulia Trisiana; Finny Fitry Yani; Fitrisia Amelin; Aumas Pabuti (Indonesian Pediatric Society, 2022)
Background Kidney damage in chronic kidney disease (CKD) disrupts the 1?-hydroxylase enzyme, preventing the conversion of vitamin D into the active form of calcitriol. To our knowledge, no previous studies have assessed calcitriol levels in children with CKD. Decreased vitamin D levels may occur at an early stage of the disease, so it is important to evaluate calcitriol levels in children with early stage CKD. Objective To assess calcitriol levels in children with CKD according to disease stage and other characteristics. Methods This cross-sectional study was conducted on 43 pediatric CKD patients at Dr. M Djamil Hospital, Padang, Indonesia. We recorded patient characteristics and performed laboratory tests, including routine hematology, blood urea nitrogen (BUN), creatinine, uric acid, electrolytes, calcium, and calcitriol levels. Based on estimated glomerular filtration rate (GFR), patients were grouped into either early-stage (stages I and II), or advanced-stage (stages III to V) CKD. Univariate and multivariate analyses were conducted to determine the association between calcitriol levels with disease stage and other characteristics. Results The overall mean calcitriol level of our subjects was 108.77 (SD 10.79) pmol/L. Mean levels at each CKD stage from I to V were 164.28 (SD 160.90), 94.14 (SD 50.63), 72.16 (SD 13.18), 62.92 (SD 4.87), and 67.51 (SD 4.87) pmol/L, respectively. Calcitriol levels did not differ significantly by CKD stage (P=0.114) when each stage from I to V was considered separately. There was no significant difference in calcitriol levels by growth characteristics (P=0.944), etiology (P=0.311), or anemic status (P=0.104). However, low calcitriol levels were found in all subjects with advanced stage CKD, compared to 63.6% subjects with early stage CKD (P=0.004). Mean calcitriol levels were significantly lower in CKD stage IV (P=0.049) and stage V (P=0.027) compared to stage I. Conclusions The decrease in calcitriol level occurs at an early stage in CKD. Calcitriol levels are significantly lower in advanced stage than in early stage CKD.